PENGARUH PENGGUNAAN INTERNET TERHADAP BISNIS ONLINE DI KEDIRI PADA MASA PANDEMI COVID-19 - Anggraini, Farida Dwi; Kholipah, Nur; luvita, Firda Alyang; Arifin, Zainal (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
Currently the Internet has been widely used by people in Indonesia. It has even become a basic necessity. Moreover, during the Covid 19 pandemic, people were required to work from home using the internet. This also applies to business actors. So we conducted this study aimed to determine the effect of internet use on online business during the Covid 19 pandemic. The sampling technique in this study used random sampling, a sample taken from a population group of business actors in Kediri. This research uses simple linear regression test method. From the results of research that has been done, it can be seen that the use of the internet on online businesses in Kediri during the pandemic has a significant effect. So it cannot be denied that the internet has an impact on the development of online businesses